High-quality development of metropolitan regions and its driving factors: A case study of the Xuzhou Metropolitan Region - ZHU Huxiao, OU Xiangjun, YANG Zhen, TANG Shuangshuang, XIAO Weidong (Ziyuan Kexue)
[Objective] The high-quality development of metropolitan regions is of great significance for promoting the transformation and upgrading of the economic structure and the construction of a new development pattern. This study aimed to clarify the connotation of high-quality development in metropolitan regions, explore the characteristics of change and driving factors of the high-quality development level of emerging metropolitan areas represented by the Xuzhou Metropolitan Region, and provide references for the construction of modern metropolitan regions. [Methods] This study first analyzed the connotation of high-quality development in metropolitan regions. Based on the panel data from 2010 to 2020, the spatiotemporal dynamic entropy method, kernel density estimation curves, and social network analysis were used to evaluate the high-quality development level of the Xuzhou Metropolitan Region from multiple dimensions. The obstacle degree model and quadratic assignment procedure (QAP) regression were used to explore its driving factors. [Results] (1) The economic and social development quality and the eco-environmental quality of Xuzhou Metropolitan Region have been steadily improved. However, there were uncoordinated growth rates among these three aspects. The spatial patterns of economic and social development quality exhibited an obvious core-periphery structure, while the eco-environmental quality showed the opposite pattern. (2) The radiation connection from the central city to the metropolitan region presented a radial network structure. Both the in-degree and out-degree were continuously increasing, but the net radiation did not change significantly. There was a positive correlation between the increase in the density of the radiation connection network and the reduction of regional development gaps. (3) Scientific and technological innovation, opening-up to the outside world, and ecological land protection were the main factors influencing the improvement of the development quality of the Xuzhou Metropolitan Region. The radiation capacity of the central city and the integration degree of the metropolitan region were increasingly affected by the differential allocation of economic and social factors and the coordinated protection of the eco-environment, while the impacts of geographical distance and administrative divisions were weakening. [Conclusion] From 2010 to 2020, the development quality of the Xuzhou Metropolitan Region steadily improved, with the radiating capacity of the central city and the level of metropolitan integration also strengthening. Based on the issues observed in the practical development of the Xuzhou Metropolitan Region and the driving factors for high-quality development, it is recommended to accelerate the enhancement of the central city’s capabilities, deepen the level of openness to the outside world, promote coordinated ecological and environmental protection within the metropolitan region, and strengthen the joint provision and sharing of public services.